Social business process management in practice: Overcoming the limitations of the traditional business process management. (9th January 2018) - Suša Vugec, Dalia; Tomičić-Pupek, Katarina; Vukšić, Vesna Bosilj
Business process management (BPM) is a well-known holistic discipline used widely in practice for managing business processes and achieving better organizational performance. However, recently, due to technological development, using a traditional approach to BPM is not enough anymore. The answer to the limitations of the traditional BPM has been found in the introduction and application of the social software principles in the management of business processes within a new and emerging area called social BPM. In order to investigate its implementation and usage within the companies, a literature review has been conducted. It confirmed that social BPM is a developing phenomenon. Overall, 31 papers with case studies dealing with the usage of social BPM have been selected for further analysis. The case studies have been analysed with regard to structure, process and content dimensions as well as risk management and crisis.